Addressing the Climate Crisis Local action in theory and practice - Howarth, Candice; Lane, Matthew; Slevin, Amanda (Springer Nature, 2022)
This open access book brings together a collection of cutting-edge insights into how action can and is already being taken against climate change at multiple levels of our societies, amidst growing calls for transformative and inclusive climate action. In an era of increasing recognition regarding climate and ecological breakdown, this book offers hope, inspiration and analyses for multi-level climate action, spanning varied communities, places, spaces, agents and disciplines, demonstrating how the energy and dynamism of local scales are a powerful resource in turning the tide. Interconnected yet conceptually distinct, the book's three sections span multiple levels of analysis, interrogating diverse perspectives and practices inherent to the vivid tapestry of climate action emerging locally, nationally and internationally. Delivered in collaboration with the UK's 'Place-Based Climate Action Network', chapters are drawn from a wide range of authors with varying backgrounds spread across academia, policy and practice.